Not only a therapeutic target; mTOR in Hodgkin lymphoma and acute lymphoblastic leukemia - Cuéllar Mendoza, Miguel Enrique; Chávez Sánchez, Francisco Raúl; Dorantes Acosta, Elisa María; Niembro Zúñiga, Ana María; Pelayo, Rosana; Zapata Tarrés, Marta (Frontiers in Oncology, 2024)
Introduction. The mechanistic/mammalian target of rapamycin (mTOR) is a serine/threonine kinase, when is downregulated or upregulated is implicated in different types of cancer including hematologic neoplasms, skin prostate and head and neck cancer. Aim. To explore the current knowledge of mTOR signaling in acute lymphoblastic leukemia and Hodgkin lymphoma. Methods. A systematic review was performed according to PRISMA guidelines, searching PUBMED, Discovery Service for National Autonomous University of Mexico, Registro Nacional de Instituciones y Empresas Científicas y Tecnológicas (RENIECYT) and Scientific Electronic Library Online (SciELO) from 1994 to 2023 was made. A total of 269 papers were identified for acute lymphoblastic leukemia but based on specific criteria 15 were included; for Hodgkin lymphoma 110 papers were identified, but 5 were included after manual searching. Results. A total of 20 papers were evaluated, where mTOR activity is increased in patients with Hodgkin lymphoma and acute lymphoblastic leukemia by different molecular mechanisms. Conclusions. mTOR activity is increased in patients with both hematologic neoplasms and NOTCH, Interleukin 4,7 and 9, and nuclear proteins have been studied for its role in the activation of mTOR signaling.